(untitled) (Società e diritti, 2023)
The article deals with the mutual position of subsidiarity and of the Third sector in the frame of the Italian Constitution, arguing that the genuinely innovative characteristics of subsidiarity and the novelties in terms of legislation about the Third sector are systematically weakened by the pro-competitive interpretation that follow European Union law. The main issues brought about subsidiarity and about the third sector are interpreted, even by the legislator himself, as an addition to the constitutional principles not capable to affect the fundamental aspects of the market and of State administration.